Cardiovascular magnetic resonance perfusion imaging at 3-tesla for the detection of coronary artery disease: a comparison with 1.5-tesla. - Cheng, A; Pegg, T; Karamitsos, T; Searle, N; Jerosch-Herold, M; Choudhury, R; Banning, A; Neubauer, S; Robson, M; Selvanayagam, J (2007)
OBJECTIVES: This study was designed to establish the diagnostic accuracy of cardiovascular magnetic resonance (CMR) perfusion imaging at 3-Tesla (T) in suspected coronary artery disease (CAD). BACKGROUND: Myocardial perfusion imaging is considered one of the most compelling applications for CMR at 3-T. The 3-T systems provide increased signal-to-noise ratio and contrast enhancement (compared with 1.5-T), which can potentially improve spatial resolution and image quality. METHODS: Sixty-one patients (age 64 +/- 8 years) referred for elective diagnostic coronary angiography (CA) for investigation of exertional chest pain were studied (before angiogram) with first-pass perfusion CMR at both 1.5- and 3-T and at stress (140 microg/kg/min intravenous adenosine, Adenoscan, Sanofi-Synthelabo, Guildford, United Kingdom) and rest. Four short-axis images were acquired during every heartbeat using a saturation recovery fast-gradient echo sequence and 0.04 mmol/kg Gd-DTPA bolus injection. Quantitative CA served as the reference standard. Perfusion deficits were interpreted visually by 2 blinded observers. We defined CAD angiographically as the presence of > or =1 stenosis of > or =50% diameter in any of the main epicardial coronary arteries or their branches with a diameter of > or =2 mm. RESULTS: The prevalence of CAD was 66%. All perfusion images were found to be visually interpretable for diagnosis. We found that 3-T CMR perfusion imaging provided a higher diagnostic accuracy (90% vs. 82%), sensitivity (98% vs. 90%), specificity (76% vs. 67%), positive predictive value (89% vs. 84%), and negative predictive value (94% vs. 78%) for detection of significant coronary stenoses compared with 1.5-T. The diagnostic performance of 3-T perfusion imaging was significantly greater than that of 1.5-T in identifying both single-vessel disease (area under receiver-operator characteristic [ROC] curve: 0.89 +/- 0.05 vs. 0.70 +/- 0.08; p < 0.05) and multivessel disease (area under ROC curve: 0.95 +/- 0.03 vs. 0.82 +/- 0.06; p < 0.05). There was no difference between field strengths for the overall detection of coronary disease (area under ROC curve: 0.87 +/- 0.05 vs. 0.78 +/- 0.06; p = 0.23). CONCLUSIONS: Our study showed that 3-T CMR perfusion imaging is superior to 1.5-T for prediction of significant single- and multi-vessel coronary disease, and 3-T may become the preferred CMR field strength for myocardial perfusion assessment in clinical practice.